Identifying optimal candidates for induction chemotherapy among stage II–IVa nasopharyngeal carcinoma based on pretreatment Epstein–Barr virus DNA and nodal maximal standard uptake values of [(18)F]‐fluorodeoxyglucose positron emission tomography - Xie, Hao‐Jun (Cancer Med, 2020)
OBJECTIVE: This study aimed to select optimal candidates benefiting from the addition of induction chemotherapy (IC) to concurrent chemoradiotherapy (CCRT) in stage II–IVa nasopharyngeal carcinoma (NPC) based on Epstein–Barr virus (EBV) DNA and nodal maximal standardized uptake values (SUVmax‐N) of [(18)F]‐fluorodeoxyglucose positron emission tomography. PATIENTS AND MATERIALS: A total of 679 patients diagnosed with stage II–IVa (except N0) NPC were retrospectively included in this study. Overall survival was the primary endpoint. Survival differences between different groups were compared using the log‐rank test. The hazard ratio (HR) and 95% confidence interval (CI) were calculated using a multivariable Cox proportional hazards model. RESULTS: Both high levels of EBV DNA (>1500 copies/mL) and SUVmax‐N (>12.3) indicated worse survival conditions. All patients were divided into low‐ and high‐risk groups based on these two biomarkers. The risk group was an independent prognostic factor in OS, progression‐free survival (PFS), and distant metastasis‐free survival (DMFS) (all p‐values<0.05). The addition of IC to CCRT was associated with survival improvement in OS, PFS, and DMFS in high‐risk patients, while no survival difference was found between CCRT and IC+CCRT in low‐risk patients. CONCLUSIONS: Our study can help clinicians select stage II–IVa NPC patients who benefit from IC, which is important in guiding individual treatment.